2006
DOI: 10.1523/jneurosci.3883-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Striatum in Initiation and Execution of Learned Action Sequences in Rats

Abstract: To understand the role of striatum in motor sequence learning, we trained rats to perform a series of tasks measuring speed and accuracy of responding to luminance cues presented as discriminative stimuli for single nose pokes or for sequences of nose pokes in a serial reaction time task. Habit (stimulus-response) learning was measured by comparing performances when stimuli were repeated (predictable) with when they were selected randomly (unpredictable). Sequences had defined start and end points and were lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 37 publications
2
69
1
Order By: Relevance
“…The possibility that the striatum is mediating compulsive lever-pressing is in line with evidence implicating the striatum in the pathophysiology of OCD (for review see Stein, 2000) and with views on the central role of the striatum in habitual and compulsive behavior (Graybiel, 1998;Yin et al, 2004;Balleine, 2005;Everitt and Robbins, 2005;Bailey and Mair, 2006;Packard et al, 1989), although the latter have typically been related to the lateral, rather than medial, striatum. Furthermore, although the extrapolation from an animal model to the clinical condition is problematic and should be made with great caution, the results of this study support the possibility that in a subpopulation of OCD patients a primary pathology of the OFC leads to a dysregulation of the striatal serotonergic system that is manifested in compulsive behavior, and that antiobsessional/anticompulsive drugs exert their effects, in these patients, by normalizing the dysfunctional striatal serotonergic system (Joel et al, 2005a).…”
Section: Ofc Lesionmentioning
confidence: 53%
“…The possibility that the striatum is mediating compulsive lever-pressing is in line with evidence implicating the striatum in the pathophysiology of OCD (for review see Stein, 2000) and with views on the central role of the striatum in habitual and compulsive behavior (Graybiel, 1998;Yin et al, 2004;Balleine, 2005;Everitt and Robbins, 2005;Bailey and Mair, 2006;Packard et al, 1989), although the latter have typically been related to the lateral, rather than medial, striatum. Furthermore, although the extrapolation from an animal model to the clinical condition is problematic and should be made with great caution, the results of this study support the possibility that in a subpopulation of OCD patients a primary pathology of the OFC leads to a dysregulation of the striatal serotonergic system that is manifested in compulsive behavior, and that antiobsessional/anticompulsive drugs exert their effects, in these patients, by normalizing the dysfunctional striatal serotonergic system (Joel et al, 2005a).…”
Section: Ofc Lesionmentioning
confidence: 53%
“…As such, it is not surprising that multiple neural structures contribute to the generation of PIT effects (Corbit and Balleine, 2005;Corbit et al, 2001;Hall et al, 2001;Murschall and Hauber, 2006). Previous findings have emphasized a role for the dorsal striatum in the acquisition of stimulus-reward (Aosaki et al 1994) and stimulus-response associations (Jog et al, 1999;Brasted and Wise, 2004;Yin et al, 2004;Barnes et al, 2005) and in stimulusguided performance (Kawagoe et al, 1998;Tremblay et al, 1998;Adams et al, 2001;Hassani et al, 2001;Cromwell and Schultz, 2003;Samejima et al, 2005;Bailey and Mair, 2006). These findings suggest that conditioned stimuli may direct instrumental behavior through dorsal striatal circuitry.…”
Section: Introductionmentioning
confidence: 94%
“…There is a considerable body of evidence that implicated the dorsal striatum in the acquisition of cue-reward associations (Aosaki et al 1994) and in cue-guided performance (Adams et al 2001;Bailey and Mair 2006;Hassani et al 2001;Kawagoe et al 1998;Samejima et al 2005;Tremblay et al 1998). For example, the neuronal activity of striatal neurons is influenced depending on the reward magnitude signaled in advance by discriminative cues (Cromwell and Schultz 2003) and plays a critical role in maintaining reward magnitude representations to guide actions (e.g., Hikosaka et al 2006).…”
Section: Dopamine In the Pdms And Reward-dependent Modulation Of Behamentioning
confidence: 99%
“…Considerable evidence suggests that the dorsal striatum is important in mediating the impact of reward-predictive stimuli on behavior. For example, electrophysiological studies demonstrated that the dorsal striatum is involved in the acquisition of stimulus-reward (Aosaki et al 1994) and stimulus-response associations (Barnes et al 2005;Brasted and Wise 2004;Jog et al 1999;Yin and Knowlton 2004) as well as in stimulus-guided performance (Adams et al 2001;Bailey and Mair 2006;Cromwell and Schultz 2003;Hassani et al 2001;Kawagoe et al 1998;Samejima et al 2005;Tremblay et al 1998). Different subregions of the dorsal striatum play distinct roles in the modulation of behavior by reward-predictive cues.…”
Section: Introductionmentioning
confidence: 99%